Review paper Dermatotoxins synthesized by blue-green algae (Cyanobacteria) - Rzymski, Piotr; Poniedziałek, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
In this paper we have reviewed dermatotoxins produced by blue-green algae. Dermatotoxins are harmful compounds that target human skin. Blue-green algae ( Cyanobacteria ) are prokaryotic microorganisms, mainly found in the water environment – marine and freshwater. A number of species are able to synthesize several toxic substances that affect human health upon exposure to lyngbya-, aplysia- and debromoaplysiatoxin. Lipopolysaccharides present in cyanobacteria cell walls can be irritating to human skin. Therefore, surface waters for recreational use should be monitored for the presence of toxic species of blue-green algae.